Successful Treatment of Giant xanthelasma palpebrarum by carbon dioxide (CO2) laser - Urbāne, Agnese; Zavorins, Aleksejs (Dermatology Review/Przegląd Dermatologiczny, 2025)
Xanthelasma palpebrarum is the most common form of cutaneous xanthoma and represents a benign periorbital lesion characterized by the accumulation of lipid-laden cells. Giant xanthelasma is a term used to indicate xanthelasma involving all four eyelids. In this article, we report the case of a 62-year-old male diagnosed with giant xanthelasma palpebrarum. The patient was referred to a dermatologist due to extensive, yellowish plaques covering all four eyelids, which resulted in partial ptosis of the right upper eyelid. The diagnosis was confirmed histologically, and the patient underwent carbon dioxide (CO 2 ) laser ablation in three sessions, resulting in a favorable cosmetic outcome. At 7-month follow-up, the results remained stable with no signs of recurrence, visible scarring, or other delayed complications related to the procedure.